(untitled) (Journal of Engineering Studies and Research, 2015)
The issue regarding the negative impact on the human health and environment, as a result of waste storage by using improper methods remains of great actuality, especially with the increasing trend of the generated wastes quantity. The present paper aims to present the most efficient methods that can be used to reduce and prevent environmental risks caused by uncontrolled storage of agricultural waste. Will be treated theoretical aspects related to the actual state of waste management in the E.U. but also in Romania, methods of treating organic waste, as well as prevention measures of environmental risks.